Verbal and Nonverbal Text Forms of Public Service Advertisements in the Regional Government of Bone Regency - Fatimah Tahir (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This study aims to analyze the form of verbal and nonverbal texts in public service advertisements in the Regional Government of Bone Regency using the semiotics of CS Peirce. This study used descriptive qualitative method. The data is sourced from text in the PSA of the Regional Government of Bone. The data collection procedures used in this study are recording and note taking techniques. The results showed that the verbal form of PSA Local Government uses the meaning of denotation and connotation, Bugis philosophical expressions. The nonverbal text forms are dominated by the photo of the head of Regional Government, because the photo has perfect representation ability, compared to other nonverbal elements. Photos of the Bone regent and deputy regent of Bone are as icons and the logo of the local government of Bone is as a symbol. The traditional clothing that is used and the traditional house that is the setting for PSA are as indexes.